2022
DOI: 10.3389/fpsyg.2022.782033
|View full text |Cite
|
Sign up to set email alerts
|

Can a Brief Interaction With Online, Digital Art Improve Wellbeing? A Comparative Study of the Impact of Online Art and Culture Presentations on Mood, State-Anxiety, Subjective Wellbeing, and Loneliness

Abstract: When experienced in-person, engagement with art has been associated—in a growing body of evidence—with positive outcomes in wellbeing and mental health. This represents an exciting new field for psychology, curation, and health interventions, suggesting a widely-accessible, cost-effective, and non-pharmaceutical means of regulating factors such as mood or anxiety. However, can similar impacts be found with online presentations? If so, this would open up positive outcomes to an even-wider population—a trend acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 84 publications
2
11
0
Order By: Relevance
“…That participants experienced an increase in pleasantness and decrease in arousal supports the short-term mood improvement observed in participant feedback from online slow art events (Slow Art Day, 2021) as well as other studies that have indicated mood changes after art viewing in physical (Ho et al, 2015) and, more recently, online (Trupp et al, 2022) environments. But because the present study did not include a control condition that had participants viewing artworks for a more "average" viewing time of about 30 s (Carbon, 2017;J.…”
Section: Slow Looking and Moodsupporting
confidence: 77%
“…That participants experienced an increase in pleasantness and decrease in arousal supports the short-term mood improvement observed in participant feedback from online slow art events (Slow Art Day, 2021) as well as other studies that have indicated mood changes after art viewing in physical (Ho et al, 2015) and, more recently, online (Trupp et al, 2022) environments. But because the present study did not include a control condition that had participants viewing artworks for a more "average" viewing time of about 30 s (Carbon, 2017;J.…”
Section: Slow Looking and Moodsupporting
confidence: 77%
“…Although fewer studies have examined the flourishing benefits of digital art engagement than in-person art engagement, these initial studies do suggest that digital art engagement also positively affects flourishing. Viewing art on a computer has been associated with lowering negative mood (Cotter et al, under review;Trupp et al, 2021), increasing positive mood (Cotter et al, 2022;Igdalova & Chamberlain, 2022), reducing pain levels (de Tommaso et al, 2018), and elevating overall well-being (Trupp et al, 2021). Given the well-documented impact of in-person art engagement on flourishing, we examine here whether digital art engagement has similar effects.…”
Section: Examining the Flourishing Impacts Of Repeated Visits To A Vi...mentioning
confidence: 94%
“…Among the many reasons that have been provided to explain these well-being outcomes and the differential impacts of art type and context, aesthetic experience has been theorized to be key in how art viewing can impact psychological states, presumably through emotion regulation (Fancourt & Finn, 2019; Mastandrea et al, 2019; Trupp et al, 2022) and the experience of pleasure and the activation of the reward network in the brain (Mastandrea, Fagioli, & Biasi, 2019). For instance, empirical evidence indicates that appreciation of beauty was found to promote well-being, increased positive emotions, and decreased negative emotions in a randomized controlled trial web-based intervention (Martínez-Martí et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%